Current Dichotomies: Seven Reminders to Contemporary Architects - Marcelo Spina (Oz, 2014)
Ever since Robert Venturi’s influential book Complexity and Contradiction in Architecture, the word complexity has been in the horizon of architecture as a form of imaginative progress and cultural relevance. In the mid 80s and under the influence of the post-structuralist work of Jacques Derrida, the deconstructive project in architecture aimed to create visual complexity through formal collision, fragmentation, and dislocation of existing canons.